2005
DOI: 10.4321/s1130-01082005001200004
|View full text |Cite
|
Sign up to set email alerts
|

The value of abdominal ultrasound in the diagnosis of colon cancer

Abstract: Introduction: colon cancer is one of the main causes of cancer death. Diagnosis requires the examination of the entire large bowel by means of radiological or endoscopic techniques. Many patients suspect of colon cancer are referred for colonoscopy but nevertheless this suspicion is not confirmed after endoscopic examination. The objective of this study is the evaluation of the reliability of abdominal ultrasound in the diagnosis of these tumors.Material and method: we selected patients suspect of colon cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
(48 reference statements)
1
27
1
2
Order By: Relevance
“…Both studies found low specificities. The most important reasons for lower accuracy ratios with US examination as compared to endoscopy include localization of colon tumors in the rectosigmoid area and the failure of abdominal US to optimally examine this area as well as failure to demonstrate small polyps and early-phase lesions by US [10]. Our study also found a low specificity and sensitivity for US, which may be affected by the small number of patients.…”
Section: Discussioncontrasting
confidence: 38%
“…Both studies found low specificities. The most important reasons for lower accuracy ratios with US examination as compared to endoscopy include localization of colon tumors in the rectosigmoid area and the failure of abdominal US to optimally examine this area as well as failure to demonstrate small polyps and early-phase lesions by US [10]. Our study also found a low specificity and sensitivity for US, which may be affected by the small number of patients.…”
Section: Discussioncontrasting
confidence: 38%
“…Excluding evaluation of the rectal ampulla, Martínez-Ares et al achieved a sensitivity of 91.8%, specificity of 92.1%, positive predictive value of 80.9% and negative predictive value of 96.9% by considering US examination positive for malignancy when the identified mass was hypoechoic with loss of stratification and mobility of the wall. As expected, they furthermore showed that diagnosis of small polyps was not possible and that they were not resectable [5]. Like in our case, by observing the peristaltic movements, US can diagnose a substenotic or stenosis-free condition thus providing the clinician and the surgeon with information about the precise location and the cause of stenosis [6].…”
Section: Discussionmentioning
confidence: 81%
“…En lo que al diagnóstico del cáncer de colon se refiere, nuestras cifras (sensibilidad del 100%, una especificidad del 94,5%) están bastante por encima de las obtenidas por otros autores que también han usado la ecografía convencional (14)(15)(16)(17)(18)(19)(20) y están muy próximas a las obtenidas mediante ecografía hidrocolónica (21)(22)(23)(24)(25)(26). Ya en un estudio previo publicado recientemente por nuestro grupo (aunque en este caso se incluían pacientes en los que se sospechaba específicamente un cáncer de colon e incluíamos a 42 pacientes con cáncer de colon) se obtenían unas cifras de precisión diagnóstica similares (27).…”
Section: Discussionunclassified